Programa educomunicativo de pausas activas para prevención de lesiones musculoesqueléticas del Personal Administrativo Universidad Estatal de Bolívar periodo diciembre 2022 – abril 2023 - Jaña Sulca, Diego Fernando (2023)
ABSTRACT The objective of the study was to implement an active breaks program to prevent musculoskeletal injuries in the administrative staff of the State University of Bolivar during the period December 2022 - April 2023. The methodology was based on a quantitative approach, collecting data through surveys of a sample population of 145 administrative employees of the University, and then analyzing them statistically. The data showed the level of musculoskeletal injuries in administrative workers. Most of the injuries were located in the neck, dorsal region and lumbar region. Injuries to the wrists and elbows were the least frequent. Some injuries affected only one side of the body while others affected both, as in the case of the shoulders. The data could be used to identify the areas most vulnerable to injury and to implement preventive measures. They concluded that there is a moderate risk of musculoskeletal injuries. This is due to lack of physical activity and stretching exercises, in addition to poor posture at work. Most administrative workers have experienced regular upper and lower back pain, suggesting musculoskeletal injuries due to repetitive postures and movements at work. This pain has affected their efficiency and productivity, limiting their ability to work and affecting their lives. Research and educational program on active breaks to prevent musculoskeletal injuries is an important tool to improve workers' health and prevent musculoskeletal injuries. Key words: administrative employees, musculoskeletal injury, educational-communicative program, Bolivar State Universty